DEVELOPING “EXIT” GAME TO OVERCOME SENIOR HIGH SCHOOL STUDENTS’ SPEAKING ANXIETY - Titania, Fani Nabila (RETAIN, 2022)
Speaking anxiety was one serious problem for senior high school students. It should handle as soon as possible because it could affect students' learning process. This study aimed to describe the development process, the validation, and the practicality of the